Babayeva , Gunel - (:unkn) unknown (My University, 2026)
Gunel Babayeva, PhD, is a Senior Lecturer at the Department of Foreign Languages, Azerbaijan University of Architecture and Construction. She earned her Bachelor's degree in Linguistics (German) from Azerbaijan University of Languages in 2003, a Master of Arts in Foreign Language Linguistics (German as a Foreign Language and Russian) from the University of Potsdam in 2013, and a PhD from the Technical University of Berlin in 2021. Her doctoral research focused on German as a Foreign Language, with particular emphasis on teaching methodology, classroom practice, teacher competence, and learner motivation. She is the author of the monograph German as a Foreign Language in Azerbaijan (Peter Lang, 2021), as well as several scientific articles and conference papers. Before joining AzUAC in 2025, she worked as a lecturer, translator, and language educator in Azerbaijan and Germany, teaching German as a foreign and second language at universities, language centers, and public schools in Berlin. Her research interests include German language teaching, applied linguistics, translation studies, language pedagogy, and intercultural communication.